Sistem Penunjang Keputusan Rekrutmen Karyawan Baru Menggunakan Metode Weighted Product Dengan Sistem Keamanan Kode OTP Via Telegram Pada PT. Ferrindo Tata Wahana - Retno Septiyaningrum Ainun Marjuki; Ines Heidiani Ikasari (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
Recruitment is the process of accepting prospective workers to meet the need for manpower (job vacancies) in a company, while the selection process is the process of selecting the most qualified prospective workers to fill job vacancies. The process of selecting new employees at PT. Ferrindo Tata Wahana is still done manually. Starting from the personnel side, they still have to sort out the CV (Curriculum vitae) for each prospective employee. And after the file selection process, written test and interview, applicants still have to wait for get notification of the results of being accepted to work or not at the company and of course it takes quite a long time. With this decision support system, it aims to assist the company in determining new employees according to the company's needs, as well as the existence of a login security system with one time password for the login process to be more secure because the user is asked to enter a unique code before accessing the main page on the system. using the Weighted Product (WP) method of PT. Ferrindo Tata Wahana found it helpful in time because it was able to determine new employees quickly and efficiently.